1994
DOI: 10.1037/0022-3514.67.4.627
|View full text |Cite
|
Sign up to set email alerts
|

Role of consciousness and accessibility of death-related thoughts in mortality salience effects.

Abstract: On the basis of terror management theory, research has shown that subtle mortality salience inductions engender increased prejudice, nationalism, and intergroup bias. Study 1 replicated this effect (increased preference for a pro-U.S. author over an anti-U.S. author) and found weaker effects when Ss are led to think more deeply about mortality or about the death of a loved one. Study 2 showed that this effect is not produced by thoughts of non-death-related aversive events. Studies 2 and 3 demonstrated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
942
6
9

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 764 publications
(1,000 citation statements)
references
References 32 publications
43
942
6
9
Order By: Relevance
“…Then, to assess varying levels of death-related cognition, we had participants complete a measure of DTA recently used in this way by Vess et al (2009). The measure is a word completion task consisting of 28 word fragments, six of which can be completed with either a neutral or a death-related word (Greenberg, Pyszczynski, Solomon, Simon, & Breus, 1994;Mikulincer & Florian, 2000;. For example, the fragment COFF_ _ can be completed as COFFEE (a neutral word) or COFFIN (a death-related word).…”
Section: Methodsmentioning
confidence: 99%
“…Then, to assess varying levels of death-related cognition, we had participants complete a measure of DTA recently used in this way by Vess et al (2009). The measure is a word completion task consisting of 28 word fragments, six of which can be completed with either a neutral or a death-related word (Greenberg, Pyszczynski, Solomon, Simon, & Breus, 1994;Mikulincer & Florian, 2000;. For example, the fragment COFF_ _ can be completed as COFFEE (a neutral word) or COFFIN (a death-related word).…”
Section: Methodsmentioning
confidence: 99%
“…Participants consistently have not reported elevated affect in response to mortality salience inductions, and, in debriefings, they have uniformly denied any awareness that the mortality salience treatment was particularly impactful or that it affected their responses to the targets they subsequently evaluated. In addition, a recent set of studies (Greenberg et al, 1994) indicated that participants who were distracted from the topic of death after a mortality salience induction engaged in heightened worldview defense, whereas participants who were forced to keep death-related themes in consciousness did not. Among participants who simply listed whatever thoughts came to mind after the mortality salience induction, a tendency to avoid further thoughts about death was associated with higher levels of worldview defense.…”
Section: The Nature Of Mortality Salience Effectsmentioning
confidence: 99%
“…As in our prior research (e.g., Greenberg et al, 1994), we computed composite measures of evaluations of the targets--reactions to the authors and reactions to the arguments made by the authors--and conducted separate 2 (condition: mortality salience vs. control) × 2 (experimenter: informal vs. formal; between-groups) × 2 (target: pro-vs, anti-American; within-subjects) ANOVAs on each measure. The ANOVA on the author composite revealed a main effect for the target variable, with participants preferring the pro-(M = 6.31) over the anti-American (M = 3.87) target, F( 1, 43) = 80.79, p < .001.…”
Section: Resul~mentioning
confidence: 99%
See 2 more Smart Citations